Influence of agrochemicals fipronil and imidacloprid on the learning behavior of Apis mellifera L. honeybees - Carrillo, Marcela Pedraza [UNESP]; Bovi, Thaís De Souza [UNESP]; Negrão, Adriana Fava [UNESP]; Orsi, Ricardo de Oliveira [UNESP] (Editora da Universidade Estadual de Maringá (EDUEM), 2013)
Agrochemicals on crop cultivated areas is a source of contamination for bees and may cause physiological and behavioral disorders and mortality. The LD50 of the pesticides fipronil and imidacloprid was determined and their effect on the learning behavior of Apis mellifera L. honeybee evaluated. LD50 was determined by the ingestion of contaminated food with different concentrations of insecticide concentrations: Fipronil (0, 0.8, 0.4, 0.2, 0.1 and 0.05 µg bee-1) and imidacloprid (0, 0.4, 0.2, 0.1, 0.05 and 0.025 µg bee-1). The method of proboscis extension reflection (PER) and learning through citral odor evaluated their responses to food stimulation. LD50 obtained were 0.28 ± 0.11 and 0.10 ± 0.04 µg bee-1 for fipronil and imidacloprid, respectively. The PER test showed no significant difference (p < 0.05) although agrochemicals affected the learning of bees. Insecticides fipronil and imidacloprid are extremely harmful to foraging Africanized Apis mellifera bees.

O uso de agroquímicos nas áreas de cultivo representa uma fonte de contaminação para as abelhas, podendo ocasionar distúrbios fisiológicos, comportamentais e mortalidade. O objetivo do presente trabalho foi determinar a DL50 dos agroquímicos Fipronil e Imidaclopride e avaliar o efeito destes no aprendizado de abelhas Apis mellifera L. adultas. A DL50 foi determinada por meio de teste de ingestão de alimento contaminado, com diferentes concentrações dos inseticidas Fipronil (0; 0,8; 0,4; 0,2; 0,1 e 0,05 µg abelha-1) e Imidaclopride (0; 0,4; 0,2; 0,1; 0,05 e 0,025 µg abelha-1). Para avaliar as respostas ao estímulo do alimento foi utilizado o método de reflexão de extensão da probóscide (REP) e aprendizado, utilizando odor citral. As DL50 obtidas foram 0,28 ± 0,11 e 0,10 ± 0,04 µg abelha-1 para o Fipronil e Imidaclopride, respectivamente. O teste REP não apresentou diferenças significativas (p < 0,05); porém, os agroquímicos afetaram o aprendizado das abelhas. Dessa maneira, conclui-se que os inseticidas Imidaclopride e Fipronil são nocivos às abelhas campeiras de Apis mellifera.
Influência dos agroquímicos Fipronil e Imidaclopride no aprendizado de abelhas Apis mellifera L.
Keywords: apicultura; toxicidade; dose letal; beekeeping; toxicity; lethal dose